The human right to safe drinking water and sanitation. Comparative analysis from capabilities - Casas Cervantes, Abril (2023)
This study answers the question: how does the Human Right to Water and Sanitation (HRWS) materialize in the municipality of Tlajomulco, Jalisco, Mexico? and for this, the cases of two antagonistic housing developments are compared in the context of the unplanned urban growth dissociated from water management practices that prevailed throughout the country: Nueva Galicia and Silos. The first housing development evidenced problems in 2014 due to the presence of arsenic in water for domestic use above the official Mexican standard (NOM-127-SSA1-1994), which was resolved in less than a year. Thesecond development suffered from intermittent service of water of dubious quality, since 2007 that has not been resolved. This despite the fact that both developments share the same basin, the same aquifer and the same political-administrative delimitation. The methodology employed was based on three levels of analysis: city, neighborhood and domestic space, these scales summon each other and their relationships and urban dynamics are juxtaposed as layers of reality. The domestic scale is considered as a materialization space, through intense ethnographic work, of the HRWS discourse. Elements of thecapabilities approach were used, which allows analyzing the differences in terms of access to water, in the words of Nussbaum (2012): in terms of failures and omissions that are due to the presence of discrimination, where the State, due to their practices and relationships, provides water to some groups and not to others.